Preparation method of manganous-manganic oxide / graphite nano-enzyme for sensitive detection of L-cysteine

The manganese oxide/graphite nanozyme material prepared by ball milling solves the time-consuming and high-cost problems of L-cysteine ​​detection, improves the stability and catalytic activity of the material, and achieves high-sensitivity L-cysteine ​​detection.

CN120774467APending Publication Date: 2025-10-14JINING MEDICAL UNIV
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202510641619.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-05-19
Publication Date
2025-10-14

AI Technical Summary

Technical Problem

Existing technologies for L-cysteine ​​detection are time-consuming, complex, and costly. Furthermore, the structure of Mn3O4 nanomaterials is easily altered after oxidation, making their recovery and reuse difficult. Furthermore, their low electrical conductivity affects their catalytic performance.

Method used

The mechanochemical method is used to ball-mill manganese tetraoxide and graphite in a certain proportion to prepare manganese tetraoxide/graphite nanozymes, forming a metal-carbon structure, increasing the specific surface area and catalytic activity, and improving the material stability and catalytic activity through covalent bond connection.

Benefits of technology

High-sensitivity L-cysteine ​​detection was achieved at room temperature, with a detection range of 1-40 μmol/L and a detection limit of 0.361 μmol/L. The material is highly active, easy to synthesize in large quantities, and environmentally friendly.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure HDA0005408380280000011
    Figure HDA0005408380280000011
  • Figure HDA0005408380280000012
    Figure HDA0005408380280000012
  • Figure HDA0005408380280000021
    Figure HDA0005408380280000021
Patent Text Reader

Abstract

The invention relates to a preparation method of manganous-manganic oxide / graphite nano-enzyme for sensitive detection of L-cysteine, a green synthesis strategy is adopted, a mechanochemical method is combined to develop a novel Mn3O4 / graphite composite material which is low in cost, high in activity and easy to synthesize in macroscopic quantity, and the prepared product has relatively high catalytic activity and can be applied to the detection of L-cysteine. Compared with the prior art, the method has the advantages that oxidase-like activity is obviously improved, the Michaelis constant Km is 0.132, the maximum reaction rate Vmax is 0.998 * 10 <-7 > M <-1 > s, high-sensitivity and visual analysis and detection of L-Cys can be realized at normal temperature, the detection interval is 1-40 [mu] mol / L, and the detection limit is 0.361 [mu] mol / L.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a preparation method of manganese tetraoxide / graphite nanozyme for sensitive detection of L-cysteine, and belongs to the field of nano-analytical chemistry. Background Art

[0002] L-Cysteine ​​(L-Cys) is an amino acid that plays a key role in human growth. Its levels are associated with cardiovascular disease, renal function, and metabolic disorders, among other conditions. Therefore, sensitive detection of L-Cys can provide an important reference for assessing potential diseases. Currently, many analytical techniques are used to detect L-Cys, such as flow injection analysis, high-performance liquid chromatography, and fluorescence. However, these techniques require time-consuming and complex pretreatment and are costly. Therefore, there is a need to develop a simple, sensitive, and efficient method for L-Cys detection.

[0003] Nanozymes are nanocatalytic materials with inherent enzyme-like properties. Their low cost, high stability, tunability, and recyclability have attracted widespread attention in fields such as colorimetric analysis, disease diagnosis, and environmental remediation. Nanozyme-based colorimetric sensors have attracted extensive research and attention due to their advantages such as simple operation, rapid response, and high sensitivity. Nanozymes with oxidase-like activity use molecular oxygen as a substrate, eliminating the need for toxic and unstable hydrogen peroxide, thereby simplifying the sensing system and improving its stability. In the field of analytical detection, these nanozymes catalyze the production of strong oxidizing substances such as reactive oxygen species (ROS) from molecular oxygen, which in turn oxidize various chromogenic substrates. For example, they oxidize 3,3'5,5'-tetramethylbenzidine (TMB) to a blue oxidized product (ox-TMB), which has a characteristic UV absorption peak at 652 nm. In the presence of specific target species, the target species interact with the catalyst surface, affecting the generation of active ROS and, consequently, the colorimetric reaction. By measuring the change in the absorbance of the solution and according to the Lambert-Beer law of light absorption, quantitative detection and analysis of the target object can be achieved.

[0004] In order to achieve more efficient detection, the selection and design of nanozymes are key. Manganese oxide nanozymes have attracted much attention due to their environmental friendliness and low cost. In particular, manganese has five unpaired electrons and the most oxidation states. This unique electronic structure and the conversion between multiple valence states give manganese oxide nanozymes strong redox activity and efficient oxidase-like activity. Based on these characteristics, various manganese oxide nanozyme materials with excellent activity have been developed. Among manganese oxide nanozymes, Mn3O4 nanomaterials are particularly prominent, as they have more low-valent manganese ions (Mn 2+ / Mn 3+ ), and Mn 2+ 、Mn 3+ and Mn4+ The efficient valence state circulation among the three ions makes the Mn3O4 nanomaterial have a much higher oxyenzymatic activity than MnO2 and Mn2O3, and can generate ROS under the condition of containing oxygen without additional addition of hydrogen peroxide. Reducing substances such as L-Cys can consume ROS, thereby inhibiting the color reaction of the substrate TMB, and realizing high-sensitivity detection.

[0005] Although Mn3O4 nanomaterials have application potential in many fields, their structures are prone to change after oxidation reaction, leading to challenges in recycling and reuse. At the same time, the low conductivity of Mn3O4 limits the internal charge transfer, which has a negative impact on the catalytic performance. The combination of Mn3O4 nanoparticles and carbon can effectively inhibit the change of material structure.

[0006] However, traditional synthesis methods such as hydrothermal method and high-temperature calcination method have problems such as high energy consumption, strict equipment requirements and use of toxic solvents, which are difficult to meet the needs of large-scale production of nanoscale enzymes. Therefore, exploring efficient and economical synthesis strategies and developing high-activity Mn3O4 nanoscale enzyme materials have important research value and application prospect for improving the sensitivity of the analysis and detection system. SUMMARY

[0007] In view of the deficiencies of the prior art, the application provides a preparation method of a manganese tetroxide / graphite nanoscale enzyme for sensitive detection of L-cysteine.

[0008] The application is implemented by the following technical solutions:

[0009] A preparation method of a manganese tetroxide / graphite nanoscale enzyme for sensitive detection of L-cysteine, comprising the following steps:

[0010] The mixture of manganese tetroxide and graphite in a mass ratio of 1:4-10 in terms of effective components is loaded into a ball mill jar, grinding balls are added for ball milling, and then the ball milled material is taken out to obtain the manganese tetroxide / graphite nanoscale enzyme.

[0011] According to the application, preferably, the mass ratio of manganese tetroxide to graphite in terms of effective components is 1:6-10.

[0012] According to the application, preferably, the mass ratio of manganese tetroxide to graphite in terms of effective components is 1:8-10.

[0013] According to the application, preferably, the mass ratio of manganese tetroxide to graphite in terms of effective components is 1:8.

[0014] According to the application, preferably, the ball mill jar is a zirconia planetary ball mill jar, and the grinding balls are zirconia grinding balls with a diameter of 2.5-3.5 mm.

[0015] According to the application, preferably, the mass ratio of the amount of the grinding beads to the mixture is 11-9:1.

[0016] According to the application, preferably, the mass ratio of the amount of the grinding beads to the mixture is 10:1.

[0017] According to the application, preferably, the rotation speed of the ball mill tank is 450-550 rpm.

[0018] According to the application, preferably, the rotation speed of the ball mill tank is 500 rpm.

[0019] According to the application, preferably, the ball milling time is 2-3 hours.

[0020] A trimanganese tetroxide / graphite nanoscale enzyme for sensitive detection of L-cysteine is prepared by the above method.

[0021] A trimanganese tetroxide / graphite nanoscale enzyme for sensitive detection of L-cysteine has a specific surface area of 34.2-58.7 m 2 / g.

[0022] Application of the above trimanganese tetroxide / graphite nanoscale enzyme in detection of L-Cys.

[0023] According to the application, preferably, the specific application conditions are as follows:

[0024] The application concentration of the trimanganese tetroxide / graphite nanoscale enzyme is 1-2 g / L, the pH is 5.2, and the temperature is 25℃, so that the sensitive detection of L-Cys is realized, the detection interval is 1-40 μmol / L, and the detection limit is 0.361 μmol / L.

[0025] The trimanganese tetroxide / graphite material of the application activates oxygen as a nanoscale enzyme catalyst to generate ROS superoxide anion radicals for detection of L-Cys.

[0026] Technical features and advantages of the application:

[0027] 1. The trimanganese tetroxide / graphite nanoscale enzyme of the application can realize high-sensitivity, visual analysis and detection of L-Cys at room temperature, the detection interval is 1-40 μmol / L, and the detection limit is 0.361 μmol / L.

[0028] 2. The application adopts a green synthesis strategy, combines a mechanical chemical method to develop a new type of Mn3O4 / graphite composite material with low cost, high activity and easy macro-scale synthesis, the prepared product has high catalytic activity, the oxygenase-like activity is significantly improved, the Michaelis constant Km is 0.132, and the maximum reaction rate Vmax is 0.998 x 10 -7 M -1 s.

[0029] 3. The manganese tetraoxide / graphite material prepared by the present invention is a nanoscale material. Reducing the particle size by ball milling will increase the specific surface area. In addition, the ball milling ratio of manganese tetraoxide to graphite is related to the catalytic activity. When the ball milling ratio of manganese tetraoxide to graphite is increased from 1:4 to 1:8, the catalytic activity is significantly improved; when the ball milling ratio of manganese tetraoxide to graphite is further increased to 1:10, the catalytic activity is not further improved, indicating that the ball milling ratio of manganese tetraoxide to graphite is 1:8.

[0030] 4. Mn3O4 nanozyme is an environmentally friendly and cost-effective material. The present invention combines it with graphite, a material with excellent conductivity, chemical stability and mechanical properties, through high-energy ball milling to form a composite material with unique properties. Anchoring Mn3O4 nanoparticles to graphite nanosheets can not only achieve a synergistic effect between metal and carbon materials, but also greatly enhance the structural stability of the material, promote the improvement of electron transfer ability and catalytic activity. High-energy ball milling plays a key role in the preparation process. Through the action of mechanical force, the chemical bonds between the composite materials are reorganized, and at the same time, the broken material surface exposes more active sites, defect structures and active surfaces, giving the material richer physical and chemical properties, thereby significantly enhancing its adsorption of substrates, and thus enhancing the activity of oxidase-like enzymes. BRIEF DESCRIPTION OF THE DRAWINGS

[0031] Figure 1 Raman spectra of different materials.

[0032] Figure 2 N2- adsorption-desorption curves of different materials.

[0033] Figure 3 UV absorption spectra of TMB oxidized by different materials.

[0034] Figure 4 The absorbance of TMB oxidized by MG8 at different pH values.

[0035] Figure 5 The absorbance of TMB catalytic oxidation by the material at different MG8 concentrations.

[0036] Figure 6 The absorbance of TMB oxidation catalyzed by MG8 at different TMB concentrations.

[0037] Figure 7 Relationship between the inverse of TMB concentration and the maximum reaction rate.

[0038] Figure 8 Effects of tert-butanol and p-benzoquinone on the system at different concentrations.

[0039] Figure 9Electron paramagnetic resonance spectra of different systems.

[0040] Figure 10 Working curve of the system for detecting L-Cys. DETAILED DESCRIPTION

[0041] The present invention will be further described below with reference to the embodiments.

[0042] Example 1

[0043] The preparation method of manganese tetraoxide / graphite nanozyme for sensitive detection of L-cysteine ​​comprises the following steps:

[0044] A mixture of manganese tetraoxide and graphite in a mass ratio of 1:4 based on the effective ingredients, with a total mass of 5 g, was placed in a 25 mL zirconia planetary ball mill. 50 g of zirconia grinding beads with a diameter of 3 mm were added, the speed was set to 500 rpm, and the grinding time was 3 hours to obtain manganese tetraoxide / graphite nanozyme, recorded as MG4.

[0045] Example 2

[0046] The same preparation method as described in Example 1, except that:

[0047] The mass ratio of manganese tetraoxide to graphite, calculated as the active ingredient, was 1:6, and manganese tetraoxide / graphite nanozyme was prepared, which was recorded as MG6.

[0048] Example 3

[0049] The same preparation method as described in Example 1, except that:

[0050] The mass ratio of manganese tetraoxide to graphite, calculated as the active ingredient, was 1:8, and manganese tetraoxide / graphite nanozyme was prepared, which was recorded as MG8.

[0051] Example 4

[0052] The same preparation method as described in Example 1, except that:

[0053] The mass ratio of manganese tetraoxide to graphite, calculated as the active ingredient, was 1:10, and manganese tetraoxide / graphite nanozyme was prepared, which was recorded as MG10.

[0054] Comparative Example 1

[0055] 5 g of manganese manganese oxide was weighed and placed in a 25 mL zirconia planetary ball mill, 50 g of zirconia grinding beads with a diameter of 3 mm was added, the speed was set to 500 rpm, and the grinding time was 3 hours. The prepared material was abbreviated as BM Mn3O4.

[0056] The Raman spectra of the materials obtained in Examples 1-4 and Comparative Example 1 are as follows: Figure 1 As shown. Figure 1 It can be seen that at 1327cm -1 (I D ) and 1578cm -1 (I G ) Raman peaks can be found in MG4, MG6, MG8, and MG10, and the I D with I G The ratio (I D :I G ) becomes larger, indicating that the degree of defects in the material becomes stronger after ball milling. Located at 303cm -1 and 363cm -1 The characteristic peaks of manganese tetraoxide can be found in MG4, MG6, MG8, and MG10, indicating that ball milling does not change the crystal form of manganese tetraoxide. -1 The characteristic peak shifted to 642 cm after ball milling. -1 , indicating that the Mn-O bond inside the material is weakened. The nitrogen adsorption and desorption test results of the obtained manganese tetraoxide / graphite composite material are as follows Figure 2 As shown in the figure, the specific surface area of ​​BM Mn3O4 is 33.4m 2 / g, the specific surface areas of MG4, MG6, MG8 and MG10 are 58.7, 54.7, 40.5 and 34.2 m 2 / g, indicating that the specific surface area of ​​the material increases after ball milling treatment.

[0057] Experimental Example 1

[0058] The colorimetric method was used to investigate the oxidase-like activity of the materials obtained in Examples 1-4 and Comparative Example 1. The materials obtained in Examples 1-4 and Comparative Example 1 were mixed evenly with a buffer solution of a certain pH (the concentration of the material was 1.1 g / L, and the pH of the buffer solution was 5.2). TMB was added as an indicator to react under conditions of exposure to air (the concentration of TMB was 0.5 mmol / L). After shaking, the reaction solution was immediately transferred to a quartz cuvette with a width of 1 cm, and its absorption spectrum was measured using an ultraviolet-visible spectrophotometer. If the solution turned blue and showed a characteristic absorption peak at 652 nm, it was indicated that the material had oxidase-like activity. The test results are as follows: Figure 3 As shown, BM Mn3O4, MG4, MG6, MG8 and MG10 have characteristic absorption peaks at 652nm, indicating that the materials have oxidase-like activity, and the absorption spectrum of MG8 is the highest, indicating that MG8 has the highest catalytic activity. MG8 was used for subsequent experiments.

[0059] In order to further optimize its performance, the effects of reaction conditions such as system pH, catalyst dosage and TMB dosage on the activity of the system were further explored. MG8 was tested according to the above method, and the pH value of the system was changed. The absorbance of MG8 oxidized TMB at different pH values ​​was shown in Figure 2. Figure 4 ,from Figure 4 It can be seen that the optimal pH is 5.2.

[0060] Changing the application concentration of MG8 in the system, the absorbance of MG8 oxidized TMB at different application concentrations of MG8 is shown in Figure 2. Figure 5 ,from Figure 5 It can be seen that the optimal application concentration of MG8 is 1.1 g / L.

[0061] The concentration of TMB in the system was changed. The absorbance of TMB oxidized by MG8 was shown at different TMB concentrations. Figure 6 ,from Figure 6 It can be seen that the optimal concentration of TMB is 0.5 mmol / L.

[0062] The steady-state kinetics of the obtained material were analyzed and Michaelis-Menten and Lineweaver-Burk curves were drawn, as shown in Figure 7 As shown, and the formula Calculate the Michaelis constant Km for this reaction as K m 0.132mmol / L, V max 0.998 10-7M-1s, indicating that the material has a high affinity for the substrate and high catalytic performance.

[0063] Experimental Example 2

[0064] MG8 was mixed evenly with the buffer solution (the concentration of the material was 1.1 g / L, and the pH of the buffer solution was 5.2). TMB was added as an indicator for reaction (TMB concentration was 0.5 mmol / L) under the condition of exposure to air. After shaking, the reaction solution was immediately transferred to a quartz cuvette with a width of 1 cm.

[0065] In order to explore the ROS in the system, we first used different probes, tert-butanol and p-benzoquinone, to conduct a control experiment. Tert-butanol can react with hydroxyl radicals to inhibit activity, while p-benzoquinone can react with superoxide anion radicals to inhibit activity. Figure 8 It can be seen that different concentrations of tert-butanol have no significant effect on the catalytic activity of the system, indicating that the system does not produce hydroxyl radicals. However, the addition of p-benzoquinone significantly inhibits the catalytic activity, and the higher the p-benzoquinone concentration, the more the activity of the system decreases, indicating that superoxide anion radicals are produced in the system. Then, in order to further verify the existence of superoxide anion radicals, electron paramagnetic resonance tests were carried out, such as Figure 9As shown in the spectrum, the characteristic peak of superoxide anion radical was found, which further indicated that superoxide anion radical was generated in the system. After the addition of oxygen, the characteristic peak became stronger, indicating that the presence of oxygen promoted the generation of superoxide anion radical. After the addition of L-Cys, the characteristic peak disappeared, indicating that L-Cys consumed superoxide anion radical.

[0066] Experimental Example 3

[0067] The reaction temperature was room temperature, the pH value was 5.2, the TMB concentration was 0.5 mmol / L, and the MG8 concentration was 1.1 g / L. First, the oxidase-like activity of MG8 was used to oxidize TMB to blue ox-TMB. Then a series of L-Cys solutions with different concentrations were added. Since L-Cys has reducing property, it can reduce ox-TMB to TMB, so the oxidation degree of TMB becomes weaker, and the color of the reaction solution becomes lighter as the concentration of L-Cys increases. The absorbance difference of the system before and after the reaction was determined by ultraviolet visible spectrophotometer, and a standard curve with absorbance difference ΔA as the vertical coordinate and L-Cys concentration as the horizontal coordinate was established. The results are shown in Figure 10 As shown, the linear range was 1-40 μmol / L, and the detection limit was 0.361 μmol / L.

Claims

1. A method for preparing a manganese tetraoxide / graphite nanozyme for sensitive detection of L-cysteine, comprising the following steps: A mixture of manganese tetraoxide and graphite in a mass ratio of 1:4 to 10 based on the effective components is placed in a ball mill, milled with grinding beads, and then the ball-milled material is taken out to obtain manganese tetraoxide / graphite nanozyme.

2. The preparation method according to claim 1, characterized in that The mass ratio of trimanganese tetraoxide to graphite is 1:6-10 based on the effective components.

3. The preparation method according to claim 1, characterized in that The mass ratio of trimanganese tetraoxide to graphite is 1:8-10 based on the effective components.

4. The preparation method according to claim 1, characterized in that The mass ratio of trimanganese tetraoxide to graphite is 1:8 based on the effective components.

5. The preparation method according to claim 1, characterized in that The ball mill is a zirconium oxide planetary ball mill; the grinding beads are zirconium oxide grinding beads with a diameter of 2.5-3.5 mm, and the mass ratio of the grinding beads to the mixed material is 11-9:

1.

6. The preparation method according to claim 1, characterized in that The ball milling jar has a rotation speed of 450-550 rpm and a ball milling time of 2-3 hours.

7. A manganese tetraoxide / graphite nanozyme for sensitive detection of L-cysteine, prepared by the method according to any one of claims 1 to 6.

8. The manganese tetraoxide / graphite nanozyme according to claim 7, characterized in that The specific surface area of ​​manganese dioxide / graphite nanozymes is 34.2-58.7 m 2 / g, manganese tetraoxide is connected to the surface of graphite material through covalent bonds to form a metal-carbon structure.

9. Use of the manganese tetraoxide / graphite nanozyme according to claim 7 in detecting L-Cys.

10. The use according to claim 9, characterized in that The specific application conditions are as follows: When the application concentration of manganese tetraoxide / graphite nanozyme is 1-2g / L, the pH is 5.2, and the temperature is 25°C, sensitive detection of L-Cys is achieved, the detection range is 1-40μmol / L, and the detection limit is 0.361μmol / L. The manganese tetraoxide / graphite material acts as a nanozyme catalyst to activate oxygen and generate ROS superoxide anion radicals to detect L-Cys.

Citation Information

Cited By

  • Co-MOF nano-enzyme colorimetric detection method for L-Cys and application of Co-MOF nano-enzyme colorimetric detection method

    CN121783960A